Self-Esteem And Its Impact On Academic Performance Among Undergraduate Nursing Students Of Khyber Pukhtankhwa Pakistan; A Correlational Study : Self-Esteem and its Impact on Academic Performance - Khan, Salma; Anwar , Nasir; Khan, Imran; Ullah, Shakir; Suliman, Muhammad; Sultan, Amir (Pakistan Journal of Health Sciences, 2022)
Self-esteem is defined as self-value and the combination of skills and emotional states that describe how highly people respect themselves or think about themselves. Objective: To identify the correlation between self-esteem and academic performance. Methods: The study design was correlational descriptive, which was conducted from August 2022 to September 2022, with a sample size of 185 nursing students and a non-probability sampling technique. The self-esteem of the participants was assessed through a valid and reliable scale. Results: Among the study participants, the majority of the students were male (64.5%). In the collected data, the majority of students’ self-esteem was average (91.90%), while the academic performance of the participants was average (61.1%). The most frequent answers to the scale questions were "agree" and "strongly agree. The overall self-esteem of male participants was higher compared to female participants, while the 4th year students’ self-esteem was higher compared to other years' students. In the academic performance, the performance was best and average. The academic performance of males were higher than female participants. The findings show that there is no correlation between self-esteem and academic performance and also no correlation with selected demographic variables. Conclusions: The study demonstrates that students with higher self-esteem are more confident, have a lower stress level, and are energetic, good problem solvers. Senior students’ self-esteem has higher self-esteem compared to other class students